Legal Certainty of the Position of Substitute Heirs in the Compilation of Islamic Law and Its Relevance to the Principle of Inheritance Justice - Darsih Ayu Wulandari; Rachmi Sulistyarini; Siti Rohmah (State Islamic University of North Sumatra Indonesia, 2026)
This article examines the legal certainty of substitute heirs under the Compilation of Islamic Law (Kompilasi Hukum Islam/KHI) and its relevance to inheritance justice. Article 185 allows the child of an heir who dies before the testator to replace the parent’s position, but the phrases dapat digantikan and tidak boleh melebihi bagian ahli waris yang sederajat dengan yang diganti remain open to interpretation. Using normative juridical research with statutory and conceptual approaches, this study analyzes legal materials through grammatical, systematic, and teleological interpretation. The findings show that substitute heirship is conditional, derivative, and proportional: it arises when the original heir predeceases the testator and no legal impediment exists, derives from the predeceased parent’s position, and is limited by Article 185 paragraph (2). The term anaknya should include male and female grandchildren in the direct descending line, whether through a son or daughter of the testator. However, legal certainty still depends on consistent interpretation by Religious Courts. Article 185 should therefore be understood not merely as a technical inheritance rule, but as a justice-oriented form of Indonesian Islamic legal ijtihad that balances legal certainty, proportionality, substantive justice, and family protection. Its protection of descendants from social and economic vulnerability is also relevant to ḥifẓ al-nafs and ḥifẓ al-nasl.